Dimensões competitivas da estratégia de recursos humanos: importância para a gestão de negócios em empresas manufatureiras - Santos, Fernando Cesar Almada (1998)
This paper aims at proposing and conceptualizing the following competitive dimensions of the human resource strategy by using the contemporary concepts of competitive strategy and manufacturing strategy: the formation of a network based on teams, the organizational learning and the management of organizational culture. Within the strategic business management, these competitive dimensions must be established simultaneously with the business unit strategies and the competitive priorities of manufacturing strategy, i.e., quality, delivery perfomance, flexibility and cost. Four manufacturing companies of the metal mechanical industry, located at the interior of São Paulo state, have not only the competitive dimensions of their human resource strategy and the competitive priorities of their manufacturing strategies, but also their arrangement within the business unit strategies identified. The feasibility of applying the following theoretical propositions of this paper to manufacturing companies is analysed in this case study: the competitive dimensions of the human resource strategy and the arrangement of these dimensions and the competitive priorities of manufacturing strategy during the formulation of company strategies.